Assessment of poly(L‐lactide) as an environmentally benign CO2 capture and storage adsorbent. Issue 48 (2nd July 2020) - Stelitano, Sara; Lazzaroli, Victor; Conte, Giuseppe; Pingitore, Valentino; Policicchio, Alfonso; Agostino, Raffaele Giuseppe
Abstract: Carbon capture and storage (CCS) in conjunction with an increasing use of renewables provides a clean pathway to sustainable development and climate change mitigation. In selecting a low temperature CCS adsorbent, parameters such as selectivity, regeneration energy, and economicity play a crucial role. Poly(L‐lactide) (PLA) is one of the most promising materials in science and engineering, not only because it is a green polymer progressively replacing petrobased plastics, but also for its carbon dioxide (CO2 )‐philic nature that makes it a suitable candidate for greenhouse gas capture and climate change mitigation. Literature data point to PLA as a valid CCS candidate, although no direct gaseous CO2 adsorption investigation or with mild preparation/regenerative energy was reported. In the present experimental work, a deeper investigation of the adsorption/desorption properties of PLA in presence of gaseous CO2 at room temperature was undertaken by means of a home‐made Sievert‐type apparatus. The effects of pressure (0–15 bar), morphology (commercial pellets, powder, and flakes), and regenerative energy (303 and 333 K) were investigated. PLA samples were also characterized by helium picnometry to obtain skeletal density and by XRD and SEM to obtain morphological and structural information. Results show that PLA represents a valid and ecological alternative among the materials for the capture of CO2 . The PLA absorption capacity reaches 16 wt% at 15 bar and 303 K, and is closely linked to the thermal treatment, morphology, and crystalline structure of the material. Abstract :